THE EFFECT OF TRUST AND COMMITMENT ON CUSTOMER SATISFACTION AMONG PRINTING FIRMS IN NAKURU COUNTY, KENYA - Wilson, Lochomoi (Kabarak University, 2016)
Today’s marketing approaches is characterized by the narrow focus of attracting new customers and increasing the sales in order to deliver competitive advantage. As a strategic response, the business leaders are embracing approaches that aim at establishing sustainable and profitable relationships with their customers.
Keywords: TRUST AND COMMITMENT; PRINTING FIRMS